Indigenous knowledge of ecosystem services in rural communities of the Eastern Cape, South Africa - Murata, Chenai (Rhodes University, Faculty of Science, Department of Environmental Science)
This thesis is on indigenous knowledge of ecosystem services. The ecosystem service framework and its associated concepts are fairly young, having been introduced in the ecological discipline in the 1980s. The ecosystem service framework posits that the wellbeing of humans and their communities is dependent on services supplied by ecosystems. It emphasises that for the ecosystems to be able to supply the services, they need to be in a well-functioning state. This idea of well-functioning is predicated on the argument that the ecosystem service framework enjoins resource users to exercise responsible stewardship to prevent degradation and overharvesting. Moreover, the concept of dependence suggests that ecosystem services are of value to humans. The dominant means of measuring the value of ecosystem services has been the economic valuation method in which the contribution that each service makes to human wellbeing is quantified into monetary units. The framework disaggregates the services into four groups, namely provisioning, cultural, supporting and regulatory and seeks to all the pillars of human wellbeing including health, subsistence and spirituality into each of these groups. In doing all this, the framework significantly reconfigures the way we look at and present human-nature relations. This change has the potential to influence significant shifts in how ecological research and intervention programmes are conducted in the foreseeable future. However, the reality that the ecosystem service framework was formulated within, and is informed by the scientific epistemology begs the question: what do traditional rural communities who depend mainly on indigenous knowledge systems (IKS) for shaping and interoperating their relations with nature know of the ecosystem service concept? Rural communities are the ones who interact directly with nature on a day-to-day basis. This makes them a very critical component in the ecosystem service framework. Although South Africa has had studies in the ecosystem service theme, little has been done to attempt to investigate and document indigenous knowledge of ecosystem services that rural communities possess. By focusing only on scientific knowledge of ecosystem services, the South African literature does not do justice to the plural epistemologies of the ecosystem service users in the country. More importantly, the continued dearth of public information on indigenous knowledge of ecosystem services can potentially obstruct implementation of locally sensitive intervention programmes because nothing is known about how the local communities conceptualise the ecosystem service framework. All this presents a crucial gap in the South African research; one that unless effort is made to contribute towards filling it, our knowledge of how communities experience the ecosystem service framework in South Africa will remain skewed. This study set out to investigate and document indigenous knowledge of ecosystem services in order to contribute towards filling this gap. Indigenous knowledge system is an umbrella epistemic system that includes lay ecological knowledge (LEK), traditional ecological knowledge (TEK) and many other related organized systems of knowing. Although the thesis has a chapter on LEK, its primary focus was TEK because the thesis was interested in unravelling how aspects of tradition including taboos, customs, traditional rules and belief in ancestral forces influence local communities' knowledge of some key aspects of the ecosystem service framework including knowledge of various ecosystem services, valuation of ecosystem services, management of ecosystem services and perceptions of the management practices. The decision to focus on TEK was based on the reasoning that rural communities of the Eastern Cape boast a strong reputation of being traditional, recognizing ancestral spirits, legends and taboos as critical tools of knowledge generation and transmission. Using both mixed methods in some chapters and the qualitative approach alone in others, the study collected data in five villages of Mgwalana, Mahlungulu, Colana, Gogela and Nozitshena located in the north eastern part of Eastern Cape Province of South Africa, a region formerly called Transkei. The data were collected not on ecosystem services; but on the local people's knowledge of ecosystem services. Although literature was consulted, the study regarded respondents as the primary source of data, hence the findings and conclusions presented in this thesis are about what local people know about ecosystem services. The study uses critical realist theoretical lenses to interpret respondents' reports. The lenses included the principle of the separation between ontology and epistemology, the iceberg metaphor of ontology, epistemological pluralism and the hermeneutic dimension. These lenses were used to make sense of both the knowledge system of local people and the things about which their knowledge was. As part of discussing the local people's knowledge, the study sometimes refers to science. This is not because I expected them to demonstrate knowledge similar to science. Instead, it was a critical realist dialectical way of explaining what something is by demonstrating what it is not. The study made a couple of key findings that can potentially enhance the growth of the South African ecosystem service discipline. First, respondents demonstrated knowledge of ecosystem services by mentioning a range of them such as drinking water, medicinal plants, cultural plants and fuelwood and how they affect the wellbeing of humans. However, what they did not have good knowledge of is that nature services can be classified into the four groups of supporting, regulatory, cultural and provisioning. Among the four ecosystem services groups, respondents could identify two only; provisional and cultural. Second, local communities depend heavily on ecosystem services for their well-being. The services include fuelwood, construction timber, medicinal plants, wild fruits, wild fish, cultural services and thatch grass. Although they appreciate that ecosystem services have value to their wellbeing, local people found it difficult to represent the value in monetary units. The conditions that make it difficult for local people to perceive ecosystem services as commodities include the absence of well-defined property system, lack of a quantitative consumer tradition and absence of an economic conception of nature. Third, local people understand the need to keep ecosystems in a well-functioning state hence they implement several traditional practices to manage ecosystem services. These practices include taboos, designating certain resources as sacred, legends, customary law, as well as some secular practices including gelesha and stone terracing. However, it is not easy to understand how traditional management practices work because they are not empirically observable. Fourth, local people possess knowledge of the reality that if not well managed, ecosystems can undergo degradation and hence fail to supply the services needed for human wellbeing. However, they explain the causes of degradation in terms of changes observable at the empirical level and the invisible causal power of supernatural forces. The inclusion of natural forces in degradation explanations marks a departure from the scientific explanations that revolve around biophysical processes. Fifth, the use of traditional management practices such as taboos to management ecosystems is under threat at the local communities. The threat can be attributed to three groups of causes, namely changes in worldviews due to adoption of formal education and Christianity, institutional disharmony playing out between the state and local traditional leadership, and lifestyle changes. These challenges constrain the opportunity for local people to apply traditional management practices to prevent the degradation of ecosystems. The net implication of this is that it renders it difficult for researchers and policy makers to assess the effectiveness of traditional management practices because they are not being implemented in full. In light of all these findings, the thesis concludes that TEK is underlabouring for the ecosystem service framework in the sense that it is used by local communities to generate knowledge of ecological concepts and phenomena. This means that TEK does not exist for the sake of its own self. Drawing from this finding, the study proposes a framework of analysing TEK as an underlabourer for social-ecological triggers or issues. Nonetheless, there are few factors that can be sources of limitation to the study. These include the reality that it was difficult to access pure traditional knowledge because over the years the local communities have received many state-sponsored ecological intervention programmes and a possible personal bias given the reality that I grew up in a traditional household and my father was a key holder or TEK.,Thesis (PhD) -- Faculty of Science, Environmental Science, 2021,Thesis chapter to be published in 'Green and Low-Carbon Economy'. Journal available: https://ojs.bonviewpress.com/index.php/GLCE/index
Keywords: Ethnoscience -- South Africa -- Eastern Cape; Ecosystem management -- South Africa -- Eastern Cape; Nature -- Effect of human beings on -- South Africa -- Eastern Cape; Human ecology -- South Africa -- Eastern Cape; Human beings -- Effect of environment on -- South Africa -- Eastern Cape; South Africa -- Eastern Cape -- Rural conditions